Case Report: Massive Hemoptysis From a Spontaneously Regression Inflammatory Bronchial Polyp - Iwamoto, Yuichiro; Takenouchi, Haruka; Koyama, Katsumasa; Shirai, Ryo; Kaneto, Hideaki; Tomoda, Koichi (Frontiers in Medicine, 2022)
Background Bronchial inflammatory polyps are usually treated by surgical operation or with steroids and/or antibiotics, and it is quite rare that such polys spontaneously disappear without any treatment. This report shows a rare case with a bronchial inflammatory polyp which caused massive hemoptysis but spontaneously disappeared without any treatment. Case Presentation A 66-year-old man with type 2 diabetes mellitus and a history of cough and asthma suddenly developed massive hemoptysis while smoking and was brought to an emergency room in our institution. In bronchoscopy on admission, a polypoidal elevated lesion was observed in the left upper lobe bifurcation. Pulsatile hemorrhage from a polypoidal elevated lesion was observed upon stimulation of passage of the bronchoscope. Bronchoscopy performed 25 days after discharge showed no evidence of active bleeding and a tendency toward reduction of the elevated lesion. In bronchoscopy performed 106 days after the initial hospitalization, the bronchial inflammatory polyp completely disappeared. Conclusions We should bear in mind the possibility of spontaneous disappearance of bronchial inflammatory polyps causing some serious symptoms such as massive hemoptysis and repeated bloody sputum. Finally, we should select the best therapy for bronchial inflammatory polys based on each patient's background and conditions in clinical practice.